WSUDC: a prototype decision support tool for water supply systems management under drought conditions - Rossi G.; Nicolosi V.; Cancelliere A. (Drought management: scientific and technological innovations, 2008)
In order to implement an integrated approach for drought management, appropriate decision support tools are needed both in planning and operation stages. The paper presents WSUDC (Water System management Under Drought Conditions), a prototype software consisting of several modules for the reconstruction of streamflow series either in gauged or ungauged basins, the assessment of water volumes that can be diverted from a river section with fixed return period, the computation of water balance for reservoirs and diversions, the simulation of complex multipurpose water supply systems and the analysis of risk of water shortages. An application to an Italian case-study including several reservoirs and competing uses is discussed.
1. International Conference Drought Management: Scientific and Technological Innovations, 2008/06/12-14, Zaragoza (Spain)